2010
DOI: 10.1007/978-3-642-12176-0_1
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Plant Ribosome-Inactivating Proteins

Abstract: This contribution presents an updated analysis of the evolution of ribosome-inactivating proteins (RIPs) in plants. All evidence suggests that an ancestor of modern seed plants developed the RIP domain at least 300 million years ago. This ancestral RIP domain gave rise to a direct lineage of type 1 RIPs (i.e., primary type 1 RIPs) still present today in many monocots and at least one dicot. In a later stage, a plant succeeded in fusing the RIP domain to a duplicated ricin-B domain acquired from a bacterium. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 21 publications
(22 reference statements)
1
18
1
Order By: Relevance
“…Sequence analyses have shown that RIPs are widely distributed, even if not ubiquitous, in the plant kingdom (reviewed in [75]). Knowledge concerning the genomic sequences of an increasing number of RIPs has allowed for phylogenetic analysis of their evolutionary history.…”
Section: Studies Of the Genetics And Phylogenesis Of Ribosome-inacmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequence analyses have shown that RIPs are widely distributed, even if not ubiquitous, in the plant kingdom (reviewed in [75]). Knowledge concerning the genomic sequences of an increasing number of RIPs has allowed for phylogenetic analysis of their evolutionary history.…”
Section: Studies Of the Genetics And Phylogenesis Of Ribosome-inacmentioning
confidence: 99%
“…They could have provided the lectin domain for the fusion with an ancestral RIP domain developed in flowering plants 300 million years ago, thus giving rise to type 2 RIPs. With regard to type 1 RIPs, they could have originated independently through a convergent evolutionary process either from the ancestral gene or from the deletion of the lectin domain (reviewed in [75]).…”
Section: Studies Of the Genetics And Phylogenesis Of Ribosome-inacmentioning
confidence: 99%
“…Phylogenetic analysis suggested that most type 1 RIPs found in dicots are evolutionary related to type 2 RIPs [6]. The type 1 RIPs from Iris x hollandica are derived from the deletion of the lectin domain of the type 2 RIPs.…”
Section: Discussionmentioning
confidence: 99%
“…However, RIP sequences are not ubiquitous in plants. For example, no RIP sequence could be retrieved from the complete genome of Arabidopsis thaliana [6]. At present, RIPs have been reported frequently in the plant families Cucurbitaceae, Euphorbiaceae, Sambucaceae, Phytolaccaceae, Poaceae, and Caryophyllaceae [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation